Third-degree nasal tip burn in a preterm infant treated with amniotic membrane (Case report) - Paula Andrea Pérez Franco; Sebastian Murcia Espino; María Paula Ruiz Díaz; Juan David Rodríguez Parra (Burns Open)
Introduction: Non-fatal burns are a global health issue with a considerable impact on morbidity as well as aesthetic and functional sequelae. Facial burns in neonates are rare and often occur in hospital settings due to medical devices. Due to its regenerative potential, the amniotic membrane has been used as an alternative treatment for superficial and partial-thickness burns. This report documents the successful use of the amniotic membrane in treating a third-degree burn on the nasal tip of a preterm newborn. Case presentation and results: A male newborn at 33 weeks of gestation was admitted to the neonatal care unit and presented with a third degree burn on the tip, right ala, and columella of the nose, secondary to the use of malfunction on the temperature modulator of a ventilation mask. Initially, the use of hydrogel and dressings with Fitostimoline applied on the injury helped to partially eliminate the necrotic tissue, and then an amniotic membrane was placed on the injury. The 8-month follow-up showed adequate epithelialization without nasal collapse and a satisfactory aesthetic outcome were observed, although there was a slight loss of nasal tip projection. Discussion: This case report demonstrates the effectiveness of the amniotic membrane in the healing process of nasal burns in neonates by improving wound healing and contributing to fibrosis reduction, due to its richness in growth factors and cytokines. Its anti-inflammatory and bacteriostatic effects contribute to pain control and reduce microbial proliferation, optimizing aesthetic outcomes. In combination with other dressings, the amniotic membrane promotes neovascularization and epithelialization preventing significant deformities. Conclusion: The amniotic membrane is an effective alternative for treating neonatal facial burns, minimizing tissue damage and preserving nasal anatomy. This case report results highlight the importance of a multidisciplinary approach in treating facial burns, integrating surgical techniques and advanced wound care technologies to achieve adequate functional and aesthetic outcomes. However, long-term follow-up will establish the need for additional procedures and the evolution of the nasal anatomy.